Stellar Loci. VIII. Photometric Metallicities for 100 Million Stars Based on Synthetic Gaia Colors - Bowen Huang; Haibo Yuan; Shuai Xu; Kai Xiao; Maosheng Xiang; Yang Huang; Timothy C. Beers (The Astrophysical Journal Supplement Series)
We apply the stellar locus method to synthetic ( BP – RP ) _XPSP and ( BP – G ) _XPSP colors derived from corrected Gaia BP/RP (XP) spectra to obtain precise estimates of metallicity for about 100 million stars in the Milky Way (34 million giants in the color range 0.6 < ( BP – RP ) _0  < 1.75 and 65 million dwarfs in the color range 0.2 < ( BP – RP ) _0  < 1.5). The submillimagnitude precision of the derived synthetic stellar colors enables estimates of metallicity for stars as low as [Fe/H] ∼ −4. Multiple validation tests indicate that the typical metallicity precision is between 0.05 and 0.1 dex for both dwarfs and giants at [Fe/H] = 0, as faint as G  ∼ 16, and decreases to 0.15–0.25 dex at [Fe/H] = −2.0. For −4.0 < [Fe/H] < −3.0, the typical metallicity precision decreases to on the order of 0.4–0.5 dex, based on the results from the reference sample. Our achieved precision is comparable to or better than previous efforts using the entire XP spectra and about 3 times better than our previous work based on Gaia EDR3 colors. This opens up new opportunities for investigations of stellar populations, the formation and chemical evolution of the Milky Way, the chemistry of stars and star clusters, and the identification of candidate stars for subsequent high-resolution spectroscopic follow-up. The catalog is publicly available at doi: https://doi.org/10.12149/101548 .